Digital Zakat Fundraising in Times of Covid-19 Pandemic: Evidence from BAZNAS, Indonesia - Zulfikar Hasan; Kamiluddin Kamiluddin (Journal of Islamic Economic and Business Research, 2021)
This research analysed the impact of COVID19 on zakat institutions. The COVID19 outbreak forced policymakers to issue various innovations to manage the pandemic consequences. BAZNAS of the Republic of Indonesia has introduced its digital zakat platforms to facilitate muzaki in performing zakat. The collection of zakat funds at BAZNAS of the Republic of Indonesia has increased despite the COVID19 pandemic. This study employed a qualitative method by analyzing primary and secondary data. The results of this study concluded that the role of digital technology during the pandemic to collect zakat funds greatly facilitates muzaki. Besides that, it has received full support from the MUI (Indonesian Ulema Council) and the government. Hopefully, typical research like this that can raise more themes about the role of zakat during the COVID19 pandemic.